Three-Dimensional Flight Simulator Takeoff Movement on Boeing 737-300 Aircraft - Irfan, Muhammad; Retnowati, Nurcahyani Dewi; Adiputra, Bangga Dirgantara (Compiler, 2019)
The simulator is a form of imitation of conditions describing a behavior in conformity with the reality in which there is an interaction between the user and the simulation. Simulators are very useful for simulating events that can help the teaching and learning system. The result of this final project is a 3D take off simulator on a desktop-based Boeing 737-300 that serves as a training aid and contains an explanation of Boeing 737-300 take off information. This simulator provides ideal data in the form of weight, take off speed, flap settings and distance data to understand the aircraft performing the V1, VR and V2 processes. The research methods carried out include modeling a Boeing 737-300 aircraft using blueprint, asset modeling, and texturing using Blender 3D software then proceed with the design of simulations using Unity software. Simulation tests include black box testing. The results of the black box testing indicate that all functions of the simulator run according to the Windows 7, Windows 8, and Windows 10 operating system with a 64-bit system. Flight simulator is functioning properly and can show information on the movements and conditions od the aircraft in taking flight in the takeoff phase with weight conditions, the speed at which the aircraft drove on the runway, wind pressure conditions on the runway and flaps that will be arranged in this flight simulator.